Boron poisoning of (La, Sr)(Co, Fe)O3 cathodes of solid oxide fuel cells - Chen, K.; Hyodo, J.; Zhao, L.; Ai, N.; Ishihara, T.; Jiang, San Ping (Electrochemical Society Inc., 2013)
Effect of volatile boron species on the properties of La 0.6Sr0.4Co0.2Fe0.8O3 (LSCF) cathode materials has been studied in detail by using porous electrode coatings and dense bar samples. Prior to the characterization, the LSCF samples were heat-treated at 800°C in air in the presence of borosilicate glass for 7 and 30 days. Heat-treatment in the presence of glass has a significant detrimental effect on the surface exchange rate, electrical properties, and electrochemical activity of the cathodes. Secondary ion mass spectroscopy (SIMS) detected the deposition of boron as well as sodium and potassium on the surface and in the bulk of the bar samples. The boron deposition results in significant microstructure and composition changes. Sr in the form of SrB2O 4 is enriched on the outmost surface of LSCF bar samples, leading to the Srdeficient in the adjacent layer in the bulk. The present study demonstrates the remarkable detrimental effect of volatile boron species on the microstructure and electrochemical activity degradation of the LSCF cathode materials of solid oxide fuel cells. ©The Electrochemical Society.